DINAMIKA MANAJEMEN PERSEDIAAN MENGHADAPI TANTANGAN LOGISTIK EKSPOR DAN DAMPAKNYA TERHADAP KINERJA KEUANGAN PADA PT. X - Inang Suryani (Yayasan Nusantara Hasana Berdikari, 2025)
Inventory management is a key determinant of operational efficiency and financial stability for exporting firms, particularly agricultural commodities exposed to logistics disruption. This study examines the inventory management dynamics of PT. X for 2020–2024 and tests the effects of Inventory Turnover (ITO) and Days Inventory Outstanding (DIO) on Return on Assets (ROA) and working capital. Using a longitudinal embedded single-case approach with descriptive analysis and linear regression, the findings indicate that the 2021 surge in global freight costs coincided with a significant rise in DIO and a longer cash conversion cycle. Regression results suggest that ITO is positively related to ROA (β = 0.383), while higher DIO weakens liquidity and working capital. The results highlight inventory efficiency as a strategic lever to sustain profitability and financial resilience amid supply-chain uncertainty.